Nuts, bihexagonal, self-locking, MJ threads, classifications: 1100 MPa (at ambient temperature)/425°C, 1100 MPa (at ambient temperature)/650°C, 1210 MPa (at ambient temperature)/425°C, 1210 MPa (at ambient temperature)/730°C, 1550 MPa (at ambient temperature)/235°C, 1550 MPa (at ambient temperature)/425°C and 1550 MPa (at ambient temperature)/600°C. Dimensions. (15th June 1998) - British Standards Institution,
No abstract available